Calculation and experimental determination of the speed of advancement of the plasma leader channel of a pulse spark discharge in atmospheric air - M. I. Baranov (Electrical engineering & Electromechanics, 2024)
Goal. Calculation and experimental determination of middle speed vL of advancement of plasma leader channel of a pulse spark discharge in the long air interval of the double-electrode discharge system (DEDS) «tip-plane». Methodology. Bases of the theoretical electrical engineering and electrophysics, electrophysics bases of technique of ultra- and high-voltage and high pulse currents, bases of high-voltage pulse technique and measuring technique. Results. The close calculation and experimental method of determination of middle speed vL of advancement of plasma leader channel of an electric pulse spark discharge is offered in the long air interval of DEDS «tip-plane». This method is based on the offered calculation empiric formula for finding of the indicated speed vL and results of decoding of oscillograms of process of cut of in-use standard interconnect аperiodic pulse of over- and high-voltage of temporal shape of Tm/Тd≈200 μs/1990 μs of positive polarity at an electric hasp in indicated DEDS of long air intervals with their minimum length of lmin, numeral making 1,5 m (first case) and 3 m (second case). It is shown that middle speed vL of advancement in atmospheric air of front of plasma channel of positive leader of an electric pulse spark discharge in probed DEDS «tip-plane» for two considered applied cases at lmin=1,5 m of lmin=3 m numeral makes approximately vL≈(1±0,03)∙105 m/s. The found numeral value of this speed vL well coincides with the known experimental information for speed of advancement of vL≈105 m/s in atmospheric air of plasma channel of negative leader for a long storm spark discharge in DEDS «charged cloud-earth». It is set that for the standard interconnect аperiodic pulse of high- and ultra- voltage of temporal shape of Tm/Тd≈200 μs/1990 μs of positive polarity middle value of aggressive strength Ed of high pulse electric field in the air interval of probed DEDS «tip-plane» numeral makes minimum length of lmin=1,5 m near Ed1≈360,8 kV/m, and for his minimum length of lmin=3 m of − Ed2≈313,4 kV/m. Originality. The comfortable is developed in the use and reliable in practical realization technicians-and-engineers calculation and experimental method of research in the conditions of high-voltage electrophysics laboratory of difficult electro-discharge processes of development of leader hasp of long air intervals and determination of minimum electric durability of air insulation of electrical power engineering and electrophysics equipment on working voltage of classes of 330-1150 kV. Practical value. Application in area of industrial electrical power engineering and high-voltage pulse technique of the got numeral electrophysics results and offered calculation and experimental method of determination of middle speed vL of advancement in atmospheric air of plasma channel of leader of a long spark discharge will allow, from one side, to deepen our scientific knowledges about a long electric pulse spark discharge in an air dielectric, and, from other side, to develop high-voltage electrical power engineering and electrophysics devices with enhanceable reliability of their work both in normal operation and malfunctions.